Analysis of Net Profit Receipt Towards Production Costs at PLKT Gunungsitoli - Dedi Irawan Zebua; Serniati Zebua; Kurniawan Sarototonafo Zai (Equivalent : Journal of Economic, Accounting and Management, 2025)
This study aims to determine the net profit receipt against production costs at PLKT Gunungsitoli. This study uses a descriptive research type that is descriptive in nature. The data collection techniques used are observation and documentation techniques. In this study, researchers used qualitative descriptive analysis techniques in analyzing data. Based on the results of the study that the net profit receipt against production costs at PLKT Gunungsitoli, the researcher concluded that the net profit receipt of PLKT Gunungsitoli was positive, namely a profit of Rp. 18,096,750. However, PLKT is not looking for large profits because there is still an element of gross profit which is the difference between net sales and cost of goods sold and especially to customers who are still inadequate to order PLKT Gunungsitoli's production results. Production design planning is a process to achieve financial goals through careful work management for the sake of adequate profit continuity. This condition, it would be better maintained by PLKT Gunungsitoli in the future and it is suggested to the related leaders to be improved in order to have more efficient cooperation or synergy between the community, government, churches and certain groups in finding solutions on how in the future PLKT Gunungsitoli will remain intact in achieving greater profits so that it has a contribution to BNKP and also related parties